The effects of indoor plants and traffic noise on English reading comprehension of Chinese university students in home offices - Zhang, Yuanyuan; Ou, Dayi; Chen, Qiu; Kang, Shengxian; Qu, Guanhua (Frontiers in Psychology, 2022)
Owing to the COVID-19 pandemic, working from home promotes the importance of indoor environment qualities. With the settings and functions of home offices, an experiment was carried out to determine the interaction effects between indoor plants and traffic noise levels (TNLs) on the performance and environmental evaluations of English reading comprehension tasks (ERCTs) and the performance of short-term breaks. A sample of 22 Chinese university students (12 males and 10 females) took part in the experiment. Two visual conditions (with and without plants) and five traffic noise levels (i.e., 35, 45, 50, 55, 60 dBA TNL) were included. Participants’ accuracy rates, eye movements, mental workload, and feelings about the environment were collected. The mental fatigue recovery (MFR), visual fatigue recovery (VFR), anxiety recovery (AR), and unfriendly recovery (UR) were measured for the analysis of a 5-minute short-term break. The results demonstrate 1) plants have significant effects on ERCTs and short-term breaks, especially at 45 and 50 dBA TNL; 2) the effects of TNLs on ERCTs’ eye movements and work environment satisfaction differ by the presence of plants, e.g., the average pupil diameter (APD), lighting and layout satisfaction; 3) The effects of indoor plants on ERCT differ by the range of TNLs. In conclusion, indoor plants are beneficial to home workers engaged in ERCT when TNL does not exceed 50 dBA. The current data highlight the importance of audio-visual interaction in home offices and provide insights into the interaction mechanism between indoor plants and traffic noise.